The Family Album and its digital migration - Sarapura Sarapura, Mercedes (2014)
The following article is related to the analysis of the family album as a cultural element and its progressive transition to the digital version aimed at approaching to the micro-scenarios where take place the daily events of the individuals and is born the interpersonal communication with current technological constraints. This communication is also reflected in the album like the archives of the individual mindsets and experiences. Learning more about their contexts, -most of them like archetypes-, what occurs to the persons and their experiences makes it possible to deeply understand communication on the social level taking into account the complexity that involves the irruption of technology inside the private spaces, becoming the family album the key element where tradition and modernity converge. Tradition, considered as the cultural apex, evokes the identity,memories and death whilst modernity involves a channel and a communicative message subject to changes caused by the technological advance, conditioning the quality of the communicative process as well as having an effect on the lifestyle and culture of the people. In sum, this approach is also appropriate to define the function of photography inside the cell of a society where images play a prominent role.